Relavansi Konsep Al-Maslaha Dalam Pembentukan Kebijakan Publik - Pratama, Maulana Hafidz; Kurniawan, Andre; Cygni, Alpha; Alifah, Muhammad Nabil (Tabayyun : Journal Of Islamic Studies, 2024)
Abstract: The concept of al-Maslaha, translated as public interest or common good in Islamic thought, holds significant relevance in shaping public policy in Indonesia. This study investigates how this concept is applied within the context of Islamic law and universal values to guide inclusive and sustainable policy-making. The research outlines various approaches and challenges in implementing al-Maslaha, including in the sectors of economy, education, environment, and good governance. It also considers the role of Islamic scholars and thinkers in developing and applying this concept, and their contribution to the discourse on public policy in Indonesia.